العنف السياسي في الدولة الموحدية وأثره في تحقيق وحدة المجال السياسي المغربي - كينة, ميلودة; غانية, بشير (جامعة الوادي - University of Eloued, 2018)
The most important feature of the Almohad state )1268ـ1126(during the revolution was to follow its policy of violence against the parish, tribes and violators, and to unite Morocco under one political authority. Soon, he was confronted by a quiet skepticism among some of the tribes that threatened the emergence of a wave of rejection of Ben Tomert's leadership and ideology, which prompted him to act swiftly to block this wave and absorb its anger. Accordingly, the Almohad call of harmony has shifted to internal tension. Among the measures established for the internal violence in the Masmid district is treachery against the tribe of Hzimira and the people of Tinmel, as well as organized liquidation, without forgetting the Tumarti political doctrine based on the legislation of violence and invasion, organizing and attempting to market them with legitimate evidence The manifestations of violence varied, and differed according to different reasons, whether during the reign of Abd alMu'minibn Ali al-Kumi 1133-1163, or later successors. The question that arises is: What is the reason for the use of violence in the Almohad state?
مقال
Keywords: الدولة الموحدية، الموحدين، العنف السياسي